IDENTIFICATION OF IMMANUEL IN THE CONTEXT OF ISAIAH 7:14 - Zainal Sibagariang (Jurnal Theologia Forum STFT Surya Nusantara, 2020)
For many scholars the identification of Immanuel and his mother in Isaiah 7:14 had been a dispute for a long time. For Christian the verse Isaiah 7:14 is one of the most popular items in the foretold the future conception and birth of a child by a virgin, the â€œfulfillmentâ€ of which is described in the Gospels of Matthew and Luke with the accounts of Maryâ€™s conceiving a child of the Holy Spirit and giving birth to Jesus. However many scholar questioned refute Christianâ€™ application of this verse. The prophet Isaiahâ€™s use of the term ×¢Ö·×œÖ°×žÖ¸Ö—×” (â€˜almah) and ×¢Ö´×žÖ¼Ö¸Ö¥× ×•Ö¼×ÖµÖ½×œ (â€˜imanu'el ) in 7:14 would pose a problem. To whom Isaiahâ€™s Immanuel and his mother intended? What is the correct interpretation of the the Immanuel and his mother of this verse contextually? This research primarily uses the inductive method to arrive at answers. Through theological reflection the following steps will be taken: firstly, the background of great controversy and analysis of the word ×Ö‘×•Ö¹×ª (â€˜ot), ×¢Ö·×œÖ°×žÖ¸Ö—×” (â€˜almah), ×”Ö¸×¨Ö¸×”Ö™ (harah), and ×¢Ö´×žÖ¼Ö¸Ö¥× ×•Ö¼×ÖµÖ½×œ (â€˜imanu'el ) in its lexical-grammatical, structural, contextual aspects. From the literary context studying and historical context of the Isaiah one must accept that this prophecy has a double meaning. Firstly is the fulfillment of the prophecy in Isaiah time and secondly the eschatological fulfillment. The text cannot be understood only from Isaiah 7:14 only, but should be explored into broader text in order to be able to interpret this prophecy correctly.